Pengaruh Feeds Instagram: Mengungkap Minat Beli Mahasiswa pada Produk Makanan dan Minuman di Bandung Raya, Indonesia - Shelvira Azka Afifah (Asosiasi Ahli Administrasi Indonesia, 2024)
The rapidly evolving technology and information have driven society into the digital sphere. This phenomenon has been leveraged by businesses to capture consumer attention, particularly among students, utilizing the social media platform Instagram's feed displaying food and beverage products to boost purchasing interest in the business realm. Based on this premise, this study aims to investigate the extent to which Instagram feeds showcasing food and beverage products influence students' purchasing interest in the Bandung Raya region, Indonesia. The research methodology employed is quantitative descriptive, involving data collection through questionnaire surveys. A total of 126 respondents, who are students in the Bandung Raya area, participated in this study, with data analysis conducted using mean tests and regression analysis. The findings of this research illustrate that the portrayal of food and beverage products on Instagram significantly impacts students' purchasing interest.